2011
DOI: 10.1039/c001054p
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the electromagnetic mechanism of surface-enhanced Raman scattering: from self-assembled arrays to individual gold nanoparticles

Abstract: Surface-enhanced Raman scattering (SERS) has been intensively explored both in theory and applications and has been widely used in chemistry, physics and biology for decades. A variety of SERS substrates have been developed in order to investigate the mechanisms behind, which give rise to the enormous enhancement even enabling single molecule detection. The Raman enhancement, which involves an electromagnetic enhancement (EM) and a chemical enhancement (CM), reflects both the physical principle of light/metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
153
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(155 citation statements)
references
References 58 publications
2
153
0
Order By: Relevance
“…These facts imply that the strong SERS effects depend much more on the nanogaps in the nano-networks than on the nano-junctions between the film and the large individual gold nanoparticles. In our previous work [38], purely network-like nanoporous gold films assembled at the air-water interface also showed very strong SERS activity using Py probe molecules, confirming that nanogaps in nano-networks play the key role in the huge enhancement [4,39,40].…”
Section: Resultssupporting
confidence: 54%
“…These facts imply that the strong SERS effects depend much more on the nanogaps in the nano-networks than on the nano-junctions between the film and the large individual gold nanoparticles. In our previous work [38], purely network-like nanoporous gold films assembled at the air-water interface also showed very strong SERS activity using Py probe molecules, confirming that nanogaps in nano-networks play the key role in the huge enhancement [4,39,40].…”
Section: Resultssupporting
confidence: 54%
“…This effect would not only enhance the intensity of Raman scattering but also change the peak positions of specific Raman bands. 74 According to the predictions from vibronic coupling theory, the CT effect is allowed for the a 1 bands, 75,76 and a non-negligible CT activity of the a 1 mode has also been reported in previous studies.…”
Section: Nano Lettersmentioning
confidence: 99%
“…Fig. 6 shows the measured Raman spectra of R6G with the concentrations of 10 -7 , 10 -10 , and It has been well demonstrated that the high SERS sensitivity can be ascribed dominantly to the abundance of nanogaps between noble metal nanoparticles, which generates high density hot spots responsible for electromagnetic enhancement [7,8,12].…”
Section: Resultsmentioning
confidence: 98%